Improving Beginning Writing Abilty through Kinetic Sand Media in Grade 2 Severely Deaf Children at SLBN 1 Lima Kaum - Dwi Astaningsih; Zulmiyetri Zulmiyetri; Asep Ahmad Sopandi; Johandri Taufan; Retno Triswandari (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to improve initial writing skills in profoundly deaf students at SLBN 1 Lima Kaum by using kinetic sand educational media. This study employs a quantitative methodology, utilizing experimental techniques through Single Subject Research (SSR) with an A-B-A design.. Data was analyzed using visual analysis in the form of graphs. Data collection techniques include tests and data collection tools in the form of test questions. The subjects of this research were grade 2 profoundly deaf students at SLBN 1 Lima Kaum.